2012
DOI: 10.2165/11632470-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Besifloxacin Ophthalmic Suspension 0.6% Administered Twice Daily for 3 Days in the Treatment of Bacterial Conjunctivitis in Adults and Children

Abstract: Registered at ClinicalTrials.gov as NCT00972777.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 40 publications
4
39
0
1
Order By: Relevance
“…56 In each of these studies, clinical efficacy was demonstrated for patients with culture-confirmed bacterial conjunctivitis when pooling infections by all causative pathogens (Table 1) and also in the following subsets: infections due to Gram-positive pathogens; infections due to Gram-negative infections; and infections due to H. influenzae, S. pneumoniae, S. aureus, or S. epidermidis, the most prevalent bacterial pathogens in these studies. Based on data from thrice-daily studies, besifloxacin ophthalmic suspension 0.6% was initially approved in 2009 for treatment of bacterial conjunctivitis due to these species as well as some less frequent causative species encountered in these studies, including CDC coryneform group G, Corynebacterium pseudodiphtheriticum, Corynebacterium striatum, Moraxella lacunata, Staphylococcus hominis, Staphylococcus lugdunensis, Streptococcus mitis group, Streptococcus oralis, and Streptococcus salivarius.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…56 In each of these studies, clinical efficacy was demonstrated for patients with culture-confirmed bacterial conjunctivitis when pooling infections by all causative pathogens (Table 1) and also in the following subsets: infections due to Gram-positive pathogens; infections due to Gram-negative infections; and infections due to H. influenzae, S. pneumoniae, S. aureus, or S. epidermidis, the most prevalent bacterial pathogens in these studies. Based on data from thrice-daily studies, besifloxacin ophthalmic suspension 0.6% was initially approved in 2009 for treatment of bacterial conjunctivitis due to these species as well as some less frequent causative species encountered in these studies, including CDC coryneform group G, Corynebacterium pseudodiphtheriticum, Corynebacterium striatum, Moraxella lacunata, Staphylococcus hominis, Staphylococcus lugdunensis, Streptococcus mitis group, Streptococcus oralis, and Streptococcus salivarius.…”
Section: Discussionmentioning
confidence: 91%
“…Individual study results have been published previously. [53][54][55][56] The active comparator study 55 and two of the vehicle-controlled studies 53,54 employed a 5-day thrice-daily treatment regimen, while the third vehicle-controlled study 56 employed a 3-day twice-daily treatment regimen (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations